2013
DOI: 10.1021/es4040045
|View full text |Cite
|
Sign up to set email alerts
|

SOA Formation Potential of Emissions from Soil and Leaf Litter

Abstract: Soil and leaf litter are significant global sources of small oxidized volatile organic compounds, VOCs (e.g., methanol and acetaldehyde). They may also be significant sources of larger VOCs that could act as precursors to secondary organic aerosol (SOA) formation. To investigate this, soil and leaf litter samples were collected from the University of Idaho Experimental Forest and transported to the laboratory. There, the VOC emissions were characterized and used to drive SOA formation via dark, ozone-initiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 64 publications
(111 reference statements)
5
31
0
Order By: Relevance
“…Monoterpenes, as lipophilic and volatile compounds, can be absorbed on the lipophilic cuticle layer (Joensuu et al, 2016). Microbes living on plant surfaces can also modify VOC emissions by metabolizing plant-emitted VOCs (Farré-Armengol et al, 2016). The lowest isoprenoid fluxes were previously measured from soil with dense understorey vegetation cover (Aaltonen et al, 2013), which supports our conclusion.…”
Section: Effect Of Understorey Vegetation On Voc Fluxessupporting
confidence: 85%
See 2 more Smart Citations
“…Monoterpenes, as lipophilic and volatile compounds, can be absorbed on the lipophilic cuticle layer (Joensuu et al, 2016). Microbes living on plant surfaces can also modify VOC emissions by metabolizing plant-emitted VOCs (Farré-Armengol et al, 2016). The lowest isoprenoid fluxes were previously measured from soil with dense understorey vegetation cover (Aaltonen et al, 2013), which supports our conclusion.…”
Section: Effect Of Understorey Vegetation On Voc Fluxessupporting
confidence: 85%
“…Earlier studies have also suggested that litter and decomposers are important isoprenoid sources (Hayward et al, 2001;Asensio et al, 2007Asensio et al, , 2008Isidorov et al, 2010;Insam and Seewald, 2010;Aaltonen et al, 2013;Greenberg et al, 2012;Faiola et al, 2014). Monoterpenes can be produced simultaneously by MEP pathways in plastids and by MVK pathways in cytoplasm, and at least some fungi and bacteria are capable of activating the MEP pathway (Rohmer et al, 1993(Rohmer et al, , 1996Eisenreich et al, 1998;Walter et al, 2000;Banerjee and Sharkey, 2014).…”
Section: Seasonality and Carbon Source Impacts On Emission Rates And mentioning
confidence: 99%
See 1 more Smart Citation
“…The potential impacts of soil BVOC emissions on atmospheric chemistry are even less well understood than emission magnitudes. Faiola et al () found that litter‐derived emissions can facilitate the formation of organic aerosols in spring and autumn in a temperate pine forest. Furthermore, the potential role of soil (including litter) BVOC emissions in decreasing reactive hydroxyl radical (OH) has been hypothesized based on atmospheric chemistry models and OH reactivity measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The clear vertical gradient indicates emission sources of α-pinene near the forest floor. In fact, emission of monoterpene from the soil surface including fallen needles/branches and roots has been suggested as an important source of α-pinene (e.g., Hayward et al, 2001;Lin et al, 2007;Aaltonen et al, 2011) and its oxidation products in aerosols (Faiola et al, 2014). The vertical gradient of α-pinene found in the present study suggests that α-pinene is emitted not only from L. kaempferi leaves but also from the forest floor, such as from litter and/or roots.…”
Section: α-Pinenementioning
confidence: 49%